Mathematical Modeling of New Algorithms for Single-Phase Earth Faults Protection in a Compensated Electrical Network - Syvokobylenko V. F.; Lysenko V. A. (Problems of the Regional Energetics, 2019)
New algorithms have been developed for selective protection against phase-to-earth faults in power supply systems of 6–35 kV. In such, due to the impact of an arc-suppressing compensating reactor (Petersen coil), the selective action of traditional protection devices is not ensured. The purpose of the work is to develop new algorithms for selective protection against phase-to-earth faults in power supply systems with Petersen coil. Mathematical modeling showed that at frequencies of 200–400 Hz, the Petersen coil practically does not reduce the capacitive current in the damaged junction when the phase is shorted to ground, unlike in the case of fundamental frequency. Therefore, to protection device current and voltage with a frequency of 300 Hz are used. This current and voltage are extracted from the current and voltage of zero-sequence using band-pass frequency filters and are used to determine the direction of reactive power. Scientific novelty comprises determining the direction of reactive power using both the current and voltage after the filters, and also their derivatives, which significantly improves the sensitivity and stability of the relay; the performance of filters being controlled depending on the instantaneous values of the zero sequence voltage amplitude, which ensures the stability of the filters; the implementation of a two-channel protection relay for receiving a constant (instead of a pulsating) signal at the output device. The effectiveness of the developed protection is confirmed by the results of the mathematical modeling, tests on a laboratory bench and the supply of full-scale signals registered by the recorders in real networks.